Hvordan påvirker IFRS 9 bankenes tapsføring i dårlige tider?; How does IFRS 9 affect banks' impairment recognition in bad times? - Henrik Andersen; Ida Nervik Hjelseth (Norges Bank, 2019)
– IFRS 9 has changed the way banks recognise credit losses. Under IFRS 9, credit impairment shall be based on more forward-looking assessments by including recognition of expected credit losses. The purpose of this memo is to analyse how IFRS 9 affects the path of Norwegian banks' credit losses in bad times. We analyse the effects of IFRS 9 by calculating and comparing the paths of banks' credit losses under IAS 39 and IFRS 9 in the period 2001-2017. Our results suggest that IFRS 9 may increase impairment losses both immediately prior to and during bad times with increased credit risk.
hdl:11250/2653106
Keywords: 330; IFRS 9; IAS 39; credit losses; enterprises; credit risk